2016
DOI: 10.1155/2016/8608462
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Static Magnetic Field on Oxidant/Antioxidant Parameters in Cancerous and Noncancerous Human Gastric Tissues

Abstract: Aim. To investigate the effects of static magnetic field (SMF) on oxidant and antioxidant parameters of the cancerous and noncancerous human gastric tissues. Materials and Methods. Gastric tissues obtained from patients with gastric cancer were used in the study. SMF was created by using two static magnets. Before and after treatment with SMF, oxidant and antioxidant parameters were measured in the tissue samples. Results. In the cancerous tissue, superoxide dismutase (SOD) activity was found higher and malond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
1
3
0
1
Order By: Relevance
“…Sirmatel et al found after 1.5 T SMF exposure, total antioxidant capacity (TAC) increased significantly in 33 male volunteers [ 39 ]. Along with the increase in total antioxidant capacity, the level of lipid peroxidation was reduced ( Figure 5 F) in mice, which was consistent with Öztürk’s study, which also found that MDA levels were reduced after 60 min, 100 mT SMF exposure in 24 non-cancerous adjacent gastric tissues [ 40 ].…”
Section: Discussionsupporting
confidence: 87%
“…Sirmatel et al found after 1.5 T SMF exposure, total antioxidant capacity (TAC) increased significantly in 33 male volunteers [ 39 ]. Along with the increase in total antioxidant capacity, the level of lipid peroxidation was reduced ( Figure 5 F) in mice, which was consistent with Öztürk’s study, which also found that MDA levels were reduced after 60 min, 100 mT SMF exposure in 24 non-cancerous adjacent gastric tissues [ 40 ].…”
Section: Discussionsupporting
confidence: 87%
“…Öztürk et al 21 compared 24 cancerous gastric tissues to the same number of non-cancerous tissues also taken from the stomach. The material was obtained during surgical operations.…”
Section: Discussionmentioning
confidence: 99%
“…A change in ion balance caused by a magnetic field may thus affect DNA synthesis (25). Exposure of gastric cancer to a static magnetic field increased superoxide dismutase (SOD) activity in the cells (26). Similarly, the proliferation of fibroblasts in bleomycin-induced pulmonary fibrosis is thought to be due to increased release of PDGF-A from alveolar macrophages.…”
Section: Discussionmentioning
confidence: 99%